1983
DOI: 10.1016/s0735-1097(83)80080-1
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis poisoning: Historical and forensic aspects

Abstract: Since the introduction of digitalis into therapy approximately 200 years ago, there have been continuing admonitions concerning its toxicity. Over 400 years ago, herbalists listed the plant as being poisonous. In fiction, the homicidal use of digitalis has appeared in the writings of Mary Webb, Dorothy Sayers and Agatha Christie. Ten instances in real life of alleged homicide by digitalis and trials of the accused are listed. The drug has been used with suicidal intent rather infrequently, compared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Two children died in 1886 after taking a cough medicine containing syrup of squills, a plant containing a cardioactive glycoside [9]. More recently, McNamara et al reported serious nonfatal toxicity in a child who ingested the leaves of a day lily plant [41].…”
Section: Types Of Digitalis Intoxication In Infants and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Two children died in 1886 after taking a cough medicine containing syrup of squills, a plant containing a cardioactive glycoside [9]. More recently, McNamara et al reported serious nonfatal toxicity in a child who ingested the leaves of a day lily plant [41].…”
Section: Types Of Digitalis Intoxication In Infants and Childrenmentioning
confidence: 99%
“…Though there are several reports of homicidal administration of digitalis preparations in adults, no such reports among children have appeared in the medical literature [9].…”
Section: Types Of Digitalis Intoxication In Infants and Childrenmentioning
confidence: 99%
“…Upon learning about the natives’ use of Strophanthus kombé seeds for poison arrows to kill animals as large as a buffalo, Kirk, himself, collected kombé seeds ( 70 ) and put them in his shirt pocket where he also kept his toothbrush. After brushing his teeth, he recognized that his pulse rate soon slowed and that this effect of kombé seeds seemed very similar to that of digitalis ( 136 ). In what is surely a remarkable example of independent, parallel discovery, native South American tribes also use extracts of plants from the genus Naucleopsis , that contain Strophanthus steroids, in poison blow darts ( 137 ).…”
Section: Cardiotonic Steroids and Their Receptormentioning
confidence: 99%
“…сотрудник домов престарелых в американских штатах Нью-Джерси и Пенсильвания Чарльз Каллен отравил дигоксином 40 человек. Наперстянку использовали в мошеннических целях в 1930-х гг., когда врачи и юристы договорились применять это растение, чтобы спровоцировать на короткое время симптомы заболевания сердца и затем потребовать возмещение от страховых компаний [10].…”
Section: результаты исследования и их обсуждениеunclassified